O estágio supervisionado do Curso de Letras: uma trama enredada pelas práticas de letramento e pelas representações do trabalho docente - Farias, Luana Francisleyde Pessoa de (2017)
This doctoral research aims to analyze the supervised internship of Letters as a social practice of literacy and privileged space for training and professional development, from the analysis of the representations that emerge in texts/discourses (internship reports and interviews) produced by the main actors, (trainee teacher, teacher trainer and supervising teacher). Situated in the interpretative and qualitative paradigm, the current study is aligned with the Brazilian Applied Linguistics of a transdisciplinary nature, as it is committed to the training of future teachers, its socio-professional development and and with the understanding of the initial formation specificities of the language teacher, in order to give visibility to its different dimensions. To this end, we mobilized the following theoretical-methodological framework: i) Literacy Studies, based on contributions from Kleiman (2005; 2006; 2016), Kleiman and Reichmann (2012), Reichmann (2015; 2016), Valsechi (2016); ii) the investigations carried out within the Sociodiscursive Interactionism (SDI) scope, among them, Bronckart (1999; 2006; 2008; 2009), Bronckart and Machado (2004), Machado (2007; 2009), Machado and Bronckart (2009); iii) the contributions of Ergonomics and Clinic of Activity, in particular, the research of Clot ([1999] 2007), Faïta (2002), Amigues (2004), Saujat (2004). Thus, a case study was conducted from four internship reports produced by an intern over the two years of internship, as well as three semi-structured interviews conducted with a triad (trainee teacher, supervising teacher and teacher trainer). Forty-two (42) excerpts from the internship reports and twenty-six (26) excerpts from the interviews based on textual analysis were analyzed (BRONCKART, 1999), specifically focusing on the thematic content, belonging to the organizational level, and the modalizations, voices and person marks, belonging to the level of enunciative analysis. We conclude that the internship reports revealed the following representations: the supervised internship as a space of conflicts, negotiations and socio-professional development; the trainee teacher as the main link that unites the other actors involved (students, supervising teacher, principals, teacher trainer); supervising teachers as key actors in the process of linking and completion of the internships, which present different profiles and relationships with the teaching profession; the students, sometimes as a disinterested and undisciplined collective, sometimes belonging to classes that became the source of satisfaction and contentment for the trainee teacher; and the teacher's work, predominantly represented as a traditional pedagogical practice, since only one of the supervising teachers was cited as "interesting" and, regarding the future teacher, the description and analysis of the regencies themselves differed little from the practices of the supervising teachers observed, revealing a complex movement of denial and adherence to the observed teaching models. Regarding the interviews, we found that the supervised internship of Letters course, UEPB/Campus III, goes beyond the fixed limits of a curriculum component by becoming a multidimensional space of formation, since multiple social identities, knowledge and practices mobilized from different spheres converge on it, building a thick web which sustains one of the most conflicting and challenging moments of initial formation. In this sense, the internship was constituted as a literate social practice in which its actors act discursively establishing spaces of formation, investigation, intervention, which are in a continuous process of (re) construction.